PEMBERDAYAAN KELUARGA MISKIN MELALUI PENGUATAN DESA SIAGA, AKSES PENDIDIKAN DAN INDUSTRI RUMAH TANGGA SEBAGAI UPAYA MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT - Elly Trisnawati; Andri Dwi Hernawan; Sri Nugroho Jati (Jurnal Buletin Al-Ribaath, 2017)
Sambas district is the district with the lowest HDI among the 14 districts in West Kalimantan. The highest education level of most people is only Elementary School, while public health issues are very complex, while most families are poor. Those facts show that Kabupaten Sambas is one of the districts that need attention in development in all sectors, including health, education, and economy. Sebawi, one of the region in Sambas district, still requires efforts to improve the human resource. The aim of KKN-PPM in Sebawi is to have a community empowerment in the areas of health, education, and socio-economic. The activities included strengthening 'desa siaga', increasing access to education, and intensive mentorship for the home industry in three selected villages, namely Sepuk Tanjung, Rantau Panjang and Sebawi. The results showed that the major program such as 'desa siaga' and entrepreneurship run very well. We successfully revitalized management and operational team of 'Desa Siaga'. and also convinced the villagers to provide ambulance facility in their village. We also established a new group of entrepreneurs consisted of housewife and dropout students. We hope that the new entrepreneur group can promote economic growth in the villages.  Hopefully, the program can be sustainable and will be monitored periodically. Keywords: community empowerment, alert village, poor families